Impact on Sensory and Aromatic Profile of Low Ethanol Malbec Wines Fermented by Sequential Culture of Hanseniaspora uvarum and Saccharomyces cerevisiae Native Yeasts - Mestre Furlani, Maria Victoria; Maturano, Yolanda Paola; Gallardo, Candelaria; Combina, Mariana; Mercado, Laura Analia; Toro, Maria Eugenia; Carrau, Francisco; Vazquez, Fabio; Dellacassa, Eduardo (MDPI, 2019)
It is well known that high ethanol levels in wines adversely affect the perception of new wine consumers. Moreover, numerous issues, such as civil restrictions, health risk and trade barriers, are associated with high ethanol concentrations. Several strategies have been proposed to produce wines with lower alcoholic content, one simple and inexpensive approach being the use of new wine native yeasts with less efficiency in sugar to ethanol conversion. Nevertheless, it is also necessary that these yeasts do not impair the quality of wine. In this work, we tested the effect of sequential culture between Hanseniaspora uvarum BHu9 and Saccharomyces cerevisiae BSc114 on ethanol production. Then, the wines produced were analyzed by GC-MS and tested by a sensorial panel. Co-culture had a positive impact on ethanol reduction and sensory profile when compared to the S. cerevisiae monoculture. Wines with lower alcohol content were related to fruity aroma; moreover, color intensity was associated. The wines obtained with S. cerevisiae BSc114 in pure conditions were described by parameters linked with high ethanol levels, such as hotness and astringency. Moreover, floral profile was related to this treatment. Based on these findings, this work provides a contribution to answer the current consumers’ preferences and addresses the main challenges faced by the enological industry